Risk factors for depression and anxiety among men and women planning for pre-implantation genetic diagnosis. (26th May 2016) - Järvholm, Stina; Broberg, Malin; Thurin-Kjellberg, Ann
Abstract: Background : Previous studies have shown that women planning for in vitro fertilisation (IVF) show more distress than do men. Most studies about distress and pre-implantation genetic diagnosis (PGD) are based on women's experiences. Little is known about what are the risk factors for men and women to experience anxiety or depression when planning for PGD. Objective : The first aim was to investigate presence of symptoms of depression and anxiety in men ( n = 17) and women ( n = 19) planning for PGD and compare this to men ( n = 23) and women ( n = 24) who were planning their first IVF. The second aim was to investigate if specified risk factors could predict the presence of anxiety and depression in the PGD group. Method : Anxiety and depression were measured with the questionnaire, the Hospital Anxiety and Depressions Scale (HADS). The Swedish version of the short Sense of Coherence scale was used to measure individuals' sense of coherence. An index was created for six risk factors tested in the PGD group. Results : Low Sense of Coherence and history of miscarriage or termination were predictors of symptoms of depression among women in the PGD group. Socioeconomic risk and having a child with the genetic disease were predictors for anxiety in men. Conclusion : Women planning for PGD and IVF reported similar levels of anxiety or depression while men in the PGD group reported significantly more anxiety than men planning for IVF. Risk factors indicating depression or anxiety were found in the PGD group. The results of the present study are relevant for pre PGD counselling.